Israeli-Palestinian conflict - a catalog of problems to solve = Konflikt izraelsko-palestyński - katalog problemów do rozwiązania - Szydzisz, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Article refers to basic problem connected with Israeli-Palestinian conflict. Author divided this catalog into two groups. The first catalog includes all objective obstacles: Jerusalem issue, Jewish settlement question and Palestinian refugees concern. The second catalog is less precise Author indicates: political scene of two societies, Israel ability to manage the conflict, international conditions and mutual distrust of both Parties.
Keywords: Israeli-Palestinian conflict; Jerusalem; Jewish settlement; Palestinian refugees; konflikt izraelsko-palestyński; Jerozolima (Jerusalem); osadnictwo żydowskie; uchodźcy palestyńscy